EFEKTIVITAS PENGGUNAAN CHORD DALAM MENINGKATKAN KEMAMPUAN BELAJAR MENCIPTA LAGU ANAK USIA DINI (Class Action Research pada Guru PAUD di Kabupaten Kediri) - Itot Bian Raharjo; Warih Handayaningrum; Autar Abdillah (JADECS (Journal of Art, Design, Art Education & Cultural Studies), 2020)
Abstact: This research is motivated by the need for songs as PAUD learning media in Kediri Regency. In general, teachers only use old songs, composing song lyrics. This study uses the Class Action Research approach which was conducted from March to October 2019. The results of the data analysis included 12 respondents (80%) in the first cycle, 5 respondents (33.3%) in the second cycle, and 2 respondents (13.3%) in cycle III that has not yet reached. It can also be seen that in the third cycle, the number of respondents reached 13 people with a percentage of 86.6%. It can be concluded that the use of chords in learning to create early childhood songs was successful, the action hypothesis in this study was declared acceptable.Key Words : Chord, compose a song, Childhood Abstrak: Penelitian ini dilatarbelakangi kebutuhan lagu sebagai media pembelajaran PAUD di Kabupaten Kediri. Pada umumnya guru hanya menggunakan lagu lama, penggubahan lirik lagu. Penelitian ini menggunakan pendekatan Class Action Research yang dilaksanakan mulai Maret - Oktober 2019. Hasil analisis data terdapat 12 responden (80%) di siklus I, 5 responden (33,3%) di siklus II, dan 2 responden (13,3%) di siklus III yang belum mencapai. Dapat diketahui pula pada siklus ke III, responden yang sudah tercapai berjumlah 13 orang dengan prosentase 86,6%. Dapat disimpulkan bahwa penggunaan chord dalam belajar mencipta lagu anak usia dini berhasil, hipotesis tindakan dalam penelitian ini dinyatakan diterima. Kata Kunci: Chord, Mencipta Lagu, Anak